High‐Throughput Particle Uptake Analysis by Imaging Flow Cytometry. Issue 1 (3rd April 2017) - Smirnov, Asya; Solga, Michael D.; Lannigan, Joanne; Criss, Alison K.
Abstract: Quantifying the efficiency of particle uptake by host cells is important in the fields of infectious diseases, autoimmunity, cancer, developmental biology, and drug delivery. Here we present a protocol for high‐throughput analysis of particle uptake by imaging flow cytometry, using the bacterium Neisseria gonorrhoeae attached to and internalized by neutrophils as an example. Cells are exposed to fluorescently labeled bacteria, fixed, and stained with a bacteria‐specific antibody of a different fluorophore. Thus, in the absence of a permeabilizing agent, extracellular bacteria are double‐labeled with two fluorophores while intracellular bacteria remain single‐labeled. A spot count algorithm is used to determine the number of single‐ and double‐labeled bacteria in individual cells, to calculate the percent of cells associated with bacteria, percent of cells with internalized bacteria, and percent of cell‐associated bacteria that are internalized. These analyses quantify bacterial association and internalization across thousands of cells and can be applied to diverse experimental systems. © 2017 by John Wiley & Sons, Inc.